TRENDS OF MATHEMATICAL LOGICAL THINKING ABILITYTHROUGH THE CRA (CONCRETE-REPRESENTATIONAL-ABSTRACT) APPROACHWITH PORTFOLIO ASSESSMENT - Novaliyosi Novaliyosi; Burhanuddin Tola; Wardani Rahayu (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The use of an approach in learning can provide a change in pre-service teachers mathematical logical thinking abilities, this study aims to look at the trends of mathematical logical thinking ability with treatments using Concrete-Representational-Abstract (CRA) approach with portfolio assessment. This research is a quasi-experimental with time series design. That has been acquired by new pre-service teachers. The subject of this study consists of 37 first year undergraduate students in one of the universities in Banten province, Indonesia. Pretest and posttest data were analyzed using paired sample t-test. The instruments consisted of 4 packages of mathematical logical thinking ability for pretest and posttest with each instrument consists of 8 questions on 4 indicators. The conclusion shows that there are significant differences and improvements in mathematical logical thinking ability from time to time after treatments in learning with CRA. The development of pre-service teachers mathematical logical thinking ability after CRA has trends to increase above the trendline with the equation y = 0.5085x - 1.4316. Keyword: Concrete-Representational-Abstract (CRA), logical thinking, portfolio.